Construction of the marginality of street musicians. The case of “King Oh Beyve” - Bieletto, Natalia (Cultura y Representaciones Sociales, 2019)
This article deals with the case of the indigenous street musician from Oaxaca, Rey Oh Beyve to suggest a debate concerning the representation of the subaltern using the aural and historiographical dimensions. Connecting my own listening experience of his songs with the nascent field of aural studies, I debate the aesthetic marginalization of his music. I use concepts such as “aesthetics of purification” (Ochoa, 2006, 2014), “hearing encounters” (escucha del encuentro) (García, 2012) and “aural abjection” (Alegre y Hernández, 2018) as recourses to scrutinize the role of listening in intersubjective mechanisms of cultural disidentification. I make use of postcolonial critique to question the traditional forms of representation such as press news, audiovisual registers and photographs to debate their use in the selection of the material that makes up an archive. I conclude that the musical activity of this man tensions the frames of recognition (Butler) and that the unintelligibility of his performance in the streets can nonetheless be interpreted as a case of agency policy.